PENINGKATAN KEMAMPUAN SOFT SKILLS KEPEMIMPINAN DAN KOMUNIKASI MAHASISWA KEBIDANAN MELALUI COMMUNITY BASED MEDICAL EDUCATION (CBME) - Suryani, Evi Sri (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2015)
Community Based Medical Education (CBME) is needed to increase midwifery student’s competency. To be a professional midwife, midwifery students  have to have good hardskills and softskills so they are able to give intervention based evidence,  make good communication, make  good cooperation in team and give solution for difficult problem in midwifery service. During this time, such program implementation is not analized yet further especially in achieving softskill learning goal consist of leadership and communication. To analyze the influence of community based medical education towards increasing midwifery student’s ability of leadership and communication. The study design used mixed method with sequential explanatory strategy. The subject of this research was VI semester students of YLPP midwifery academy of Purwokerto, midwife as field and academic lecture. Quantitative sample was total sampling and qualitative sample was chosen through purposive sampling. The instrument of quantitative research used questionnaire, while the instrument of qualitative research used indeep interview method. There was influence of community based medical education towards increasing midwifery student’s ability of communication and leadership softskills that was seen from P-value (0.000) less than a (0.05) value. Keyword : Community based medical education, Leadership, Communication